Changes in circulating pro-protein convertase subtilisin/kexin type 9 levels – experimental and clinical approaches with lipid-lowering agents. (June 2019) - Macchi, C; Banach, M; Corsini, A; Sirtori, CR; Ferri, N; Ruscica, M
Regulation of pro-protein convertase subtilisin/kexin type 9 (PCSK9) by drugs has led to the development of a still small number of agents with powerful activity on low-density lipoprotein cholesterol levels, associated with a significant reduction of cardiovascular events in patients in secondary prevention. The Further Cardiovascular Outcomes Research with PCSK9 Inhibition in Subjects with Elevated Risk (FOURIER) and Evaluation of Cardiovascular Outcomes After an Acute Coronary Syndrome During Treatment With Alirocumab (ODYSSEY OUTCOMES) studies, with the two available PCSK9 antagonists, i.e. evolocumab and alirocumab, both reported a 15% reduction in major adverse cardiovascular events. Regulation of PCSK9 expression is dependent upon a number of factors, partly genetic and partly associated to a complex transcriptional system, mainly controlled by sterol regulatory element binding proteins. PCSK9 is further regulated by concomitant drug treatments, particularly by statins, enhancing PCSK9 secretion but decreasing its stimulatory phosphorylated form (S688). These complex transcriptional mechanisms lead to variable circulating levels making clinical measurements of plasma PCSK9 for cardiovascular risk assessment a debated matter. Determination of total PCSK9 levels may provide a diagnostic tool for explaining an apparent resistance to PCSK9 inhibitors, thus indicating the need for other approaches. Newer agents targeting PCSK9 are in clinical development with a major interest in those with a longer duration of action, e.g. RNA silencing, allowing optimal patient compliance. Interest has been expanded to areas not only limited to low-density lipoprotein cholesterol reduction but also investigating other non-lipid pathways raising cardiovascular risk, in particular inflammation associated to raised high-sensitivity C-reactive protein levels, not significantly affected by the present PCSK9 antagonists.